Safety and efficacy of 'dry grape extract 60‐20' when used as feed flavouring for dogs. (29th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The feed additive 'dry grape extract 60‐20' is a mixture of two extracts, one from the seed and the other from the skin of Vitis vinifera subsp. vinifera . It is intended to be used as a sensory additive (functional group: flavouring compound) in dogs. The additive 'dry grape extract 60‐20' is specified to contain ■■■■■ The applicant proposes a maximum use level of 100 mg 'dry grape extract 60‐20'/kg of complete feedingstuffs for dogs without a withdrawal period. The FEEDAP Panel was aware of case reports indicating acute toxicity for some dogs consuming grapes or raisins at exposure levels relevant to the use of 'dry grape extract 60‐20'. The FEEDAP Panel considered that rare idiosyncratic effects could be possibly responsible for the reported cases of fatality in dogs due to acute renal failure following exposure to different types of grapes. The FEEDAP Panel considered that the additive is poorly characterised. Based on the data available, the FEEDAP Panel was not able to conclude on the safety of 'dry grape extract 60‐20' when used as a feed additive for dogs. In the absence of studies to assess the safety for the user, the FEEDAP Panel could not conclude on the safety for the user when handling the additives. Since grape seed extract is used in food as flavouring, and its function in feed is essentially the same as that in food no further demonstration of efficacy was necessary.